Drive Thru Administration Service Satisfaction Model on the Impact COVID-19, New Normal Policies, and Public Service Facilities - Setyawati, Galuh; Rojuaniah, Rojuaniah (Lafadz Jaya Publisher, 2024)
The COVID-19 pandemic is a global threat to public health that causes economic disruption, this also has an impact on the government sector, especially public administration services. Public service facilities play an important role in the human resource strategy that can be implemented by the UP PKB DKI Jakarta transportation office by providing good available facilities to provide service satisfaction for the community. The purpose of this study was to improve the quality of services to the community during the COVID-19 pandemic. This type of research is quantitative with Purposive Sampling technique which is distributed through questionnaires to 105 respondents of the KIR test at the UP PKB DKI Jakarta transportation office aged 18-55 years and located in the DKI West Jakarta area. Primary data analysis was carried out using the Structural Equation Modeling (SEM) method. The results of the study obtained H1: The impact of COVID-19 has a positive effect on service satisfaction, H2: New Normal Policy has a positive effect on service satisfaction, H3: Public Service Facilities have a positive effect on service satisfaction, H4: The impact of COVID-19 has a positive effect on the New Normal Policy, H5: The New Normal Policy has a positive effect on Public Service Facilities. This research contributes to the UP PKB DKI Jakarta transportation office in maintaining and improving service satisfaction. It can be seen from several factors formed from community complaints to be evaluated optimally and measurably. For further research, researchers suggest being able to expand the research area and look for objects in other fields.